Digital Transformation in Commerce: A Review of Emerging Technologies and Business Models - Dheeraj Patel, (AG Volumes, 2025)
Digital transformation has been a significant topic in the business world in recent years. Advances in "big data analytics, blockchain technology, artificial intelligence, and the Internet of Things (IoT)" are driving digital transformation, which is radically changing global trade. business models (BMs) are among the several company activities that have been impacted by increased digitalization. It has enabled companies to work together in novel ways, leading to new product and service offerings as well as new consumer and employee engagements. The importance of digital transformation for businesses, digital transformation technologies, business models, and digital business model types were all covered in this article. It concluded that Digital transformation reshapes commerce by enhancing business productivity, efficiency, and competitiveness through emerging technologies. It enables innovation, better customer engagement, and access to external knowledge. Success depends on addressing challenges like cybersecurity, regulations, and the digital divide, while leveraging leadership, culture, and infrastructure. Strategic digital adoption is essential for sustainable growth